2017
DOI: 10.1177/1403494817705587
|View full text |Cite
|
Sign up to set email alerts
|

Homicide in the western family and background factors of a perpetrator

Abstract: Psychological instability, violence and crime were found in all these categories of familicides. Perpetrators who had committed a suicide in addition to the familicide had more often been diagnosed with depression, but they sought treatment for mental health problems less often and had violence and self-destructiveness less often in their background than in other familicide categories. Social and healthcare professionals should be more sensitive to emerging family problems and be prepared for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
1
25
0
2
Order By: Relevance
“…By contrast, in a recent review on the topic of familicide in the Western world, the authors found prior convictions and violent behavior to be prevalent across different categories of familicide offenders (Aho, Remahl, & Paavilainen, 2017). In addition, the authors noted that many familicide offenders had both displayed psychological instability and many times sought help for mental-health problems prior to the fatal eventimportant findings in the context of prevention (Aho et al, 2017). Further, personality disorders have been shown to be prevalent among familicide offenders (Liem & Koenraadt, 2008), but no clear association has been established with financial downturn, which has been hypothesized to precipitate such events .…”
Section: Filicide-suicide and Familicidementioning
confidence: 78%
See 1 more Smart Citation
“…By contrast, in a recent review on the topic of familicide in the Western world, the authors found prior convictions and violent behavior to be prevalent across different categories of familicide offenders (Aho, Remahl, & Paavilainen, 2017). In addition, the authors noted that many familicide offenders had both displayed psychological instability and many times sought help for mental-health problems prior to the fatal eventimportant findings in the context of prevention (Aho et al, 2017). Further, personality disorders have been shown to be prevalent among familicide offenders (Liem & Koenraadt, 2008), but no clear association has been established with financial downturn, which has been hypothesized to precipitate such events .…”
Section: Filicide-suicide and Familicidementioning
confidence: 78%
“…However, according to a Dutch study, individuals in the latter groups more often lack prior convictions for violent offenses, which indicates that reliance on criminal records alone is insufficient for adequate violence-risk appraisals in these special cases (Liem & Koenraadt, 2008). By contrast, in a recent review on the topic of familicide in the Western world, the authors found prior convictions and violent behavior to be prevalent across different categories of familicide offenders (Aho, Remahl, & Paavilainen, 2017). In addition, the authors noted that many familicide offenders had both displayed psychological instability and many times sought help for mental-health problems prior to the fatal eventimportant findings in the context of prevention (Aho et al, 2017).…”
Section: Filicide-suicide and Familicidementioning
confidence: 96%
“…This raises a question as to whether some of fatal accidents were familicide or extended suicide. In Finland, the number of children killed as a result of familicide is high when compared to other western world countries [25].…”
Section: Discussionmentioning
confidence: 95%
“…The remaining sources were news outlets, articles on cases of parricide (the killing of parents) or filicide (the killing of children by parents), or books on more general topics than familicide. The second review, by Aho and colleagues (2017), was based on a systematic collection of literature and overlaps with the review by Mailloux (2014) by one article (Liem & Koenraadt, 2008). The second review also included filicide in the definition of familicide, but the results are still presented separately for filicides and familicides (by the definition applied here).…”
mentioning
confidence: 99%
“…The second literature review was conducted by Aho, Remahl, and Paavilainen (2017) and focused on background factors of familicide incidents committed in Western countries.…”
mentioning
confidence: 99%